Efficacy of virtual reality exposure therapy in the treatment of PTSD: a systematic review. - Raquel Gonçalves; Ana Lúcia Pedrozo; Evandro Silva Freire Coutinho; Ivan Figueira; Paula Ventura (PLoS ONE)
The use of Information and Communication Technologies, such as virtual reality, has been employed in the treatment of anxiety disorders with the goal of augmenting exposure treatment, which is already considered to be the first-line treatment for Post-traumatic Stress Disorder (PTSD). To evaluate the efficacy of virtual reality exposure therapy (VRET) in the treatment of PTSD, we performed a systematic review of published articles using the following electronic databases: Web of Science, PubMed, PsycINFO, and PILOTS. Eligibility criteria included the use of patients diagnosed with PTSD according to DSM-IV, the use of cognitive behavioral therapy (CBT) and the use of virtual reality for performing exposure. 10 articles were selected, seven of which showed that VRET produced statistically significant results in comparison to the waiting list. However, no difference was found between VRET and exposure treatment. Of these 10, four were randomized, two were controlled but not randomized and four were non-controlled. The majority of the articles used head-mounted display virtual reality (VR) equipment and VR systems specific for the population that was being treated. Dropout rates do not seem to be lower than in traditional exposure treatment. However, there are a few limitations. Because this is a new field of research, there are few studies in the literature. There is also a need to standardize the number of sessions used. The randomized studies were analyzed to assess the quality of the methodology, and important deficiencies were noted, such as the non-use of intent-to- treat-analysis and the absence of description of possible concomitant treatments and comorbidities. Preliminary data suggest that VRET is as efficacious as traditional exposure treatment and can be especially useful in the treatment of patients who are resistant to traditional exposure.